2017
DOI: 10.1111/anec.12462
|View full text |Cite
|
Sign up to set email alerts
|

ECG‐derived Cheyne‐Stokes respiration and periodic breathing in healthy and hospitalized populations

Abstract: Background Cheyne-Stokes respiration has been investigated primarily in outpatients with heart failure. In this study we compare Cheyne-Stokes respiration (CSR) and periodic breathing (PB) between healthy and cardiac groups. Methods We compared CSR and PB, measured during 24 hours of continuous 12-lead electrocardiographic (ECG) Holter recording, in a group of 90 hospitalized patients presenting to the emergency department with symptoms suggestive of acute coronary syndrome to a group of 100 healthy ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…28 Our research group has been exploring the use of continuous ECG data to measure respiration (Figure 1) and CSRPB (Figure 2) in both community-based healthy participants and hospitalized patients with suspected acute coronary syndrome (ACS). 10 In our prior work, using 12-lead ECG Holter data, we found that hospitalized telemetry unit patients with confirmed ACS had CSR episodes 6 times more frequently and PB episodes 1.3 times more frequently than patients with a non-ACS cardiac diagnosis (i.e. valvular heart disease, heart failure, pericarditis, aortic dissection).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…28 Our research group has been exploring the use of continuous ECG data to measure respiration (Figure 1) and CSRPB (Figure 2) in both community-based healthy participants and hospitalized patients with suspected acute coronary syndrome (ACS). 10 In our prior work, using 12-lead ECG Holter data, we found that hospitalized telemetry unit patients with confirmed ACS had CSR episodes 6 times more frequently and PB episodes 1.3 times more frequently than patients with a non-ACS cardiac diagnosis (i.e. valvular heart disease, heart failure, pericarditis, aortic dissection).…”
Section: Introductionmentioning
confidence: 84%
“…This is an observational study using ECG data from two studies, one including a group of 461 ICU patients (Alarm Study General Electric Study number 123.042012-GES-0003) 35 and, the second including a group of 100 healthy community-based participants (T32 NR007088, F31 NR015196). 10 Both studies received Institutional Review Board approval, and the methods for these have been described previously. 10,35 A waiver of consent was granted for the ICU group, which allowed inclusion of all consecutive patients admitted to the ICU.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations